IMPACT OF PHYSICIAN LED LIFE STYLE MODIFICATIONS (DIET AND DAILY STEP COUNT BY USING PEDOMETER) ON GLYCEMIC CONTROL OF PATIENTS WITH TYPE II DIABETIC - Azhar, Rimsha; Uttra, Khurshid; Khan, Andaleeb; Awan, Marriam Hussain; Anwer, Ayesha; Lodhi, Muhammad Wajahat Alam; Qureshi, Muhammad Waleed Hassan (Pakistan Armed Forces medical journal, 2021)
Objective: To determine the impact of physician led life style modifications (diet and daily step count by using pedometer) on glycemic control of type II diabetic patients Study Design: Quasi experimental study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, Aug 2018 to Feb 2019. Methodology: The sample population comprised of 200 diabetic patients reporting for the routine follow-up at a tertiary care hospital in Rawalpindi. Patients were divided into two groups by random method. Group A had the patients with continuation of the routine anti-diabetic medication while group received the physician led life style modifications in addition to the routine anti diabetic medication. Values of HBA1c among the groups were compared three months after the start of study. Results: Mean age of the patients was 42.19 ± 6.175 years. Mean duration of DM in the study participants was 4.52 ± 4.166 years. Out of 115 patients were male while 85 were female. HBA1c in the intervention group was 7.96% ± 0.39 while in the control group was 7.04% ± 0.81. Difference between the two groups was statistically significant (p-value<0.01). Conclusion: This study showed a significant difference in glycemic control of patients who received physician led life style modification in addition to conventional biological treatment than those who only received the routine anti-diabetic medication. Physicians should be trained to impart this sort of education to the diabetic patients in routine diabetic clinics.